SAP SuccessFactors Talent a complete guide to configuration, administration, and best practices : succession and development; Volume 2 - Traynor, Susan; Wellens, Michael A.; Krishnamoorthy, Venki (Apress, 2021)
Take an in-depth look at SAP SuccessFactors talent modules with this complete guide to configuration, administration, and best practices. The book follows a logical progression of SAP SuccessFactors modules that should be configured to complete a comprehensive talent management solution. The authors walk you through fully functional simple implementations in the primary chapters for each module before diving into advanced topics in subsequent chapters. In volume 2, you will explore the development module in three more chapters by learning to configure and use development plans, career worksheets, and mentoring. Then, the book examines succession management, covering topics such as configuring, administering, and using the 9-box, the Talent Review form, nominations, succession org charts, talent pools, and succession presentations. The authors then sum up with a review of what you learned and final conclusions. Within each topic, the book touches on the integration points with other modules as well as internationalization. The authors also provide recommendations and insights from real world experience. Having finished the book, you will have an understanding of what comprises a complete SAP SuccessFactors talent management solution and how to configure, administer, and use each module within it. You will: Work with the career worksheet Build mentoring into your SAP SuccessFactors solution Display and update relevant talent data in a succession org chart.
Includes index. - Online resource; title from PDF title page (SpringerLink, viewed May 6, 2021)
Keywords: Personnel management -- Computer programs; Employees -- Coaching of -- Computer programs; Personnel; Direction; Logiciels; Personnel management; Computer programs